2017
DOI: 10.1007/s10064-017-1016-5
|View full text |Cite
|
Sign up to set email alerts
|

Dust formed during drilling in natural stone quarries

Abstract: Dust mass concentration and concentration decrease was studied in two natural stone quarries in Finland. The dust mass concentrations produced during drilling was measured at several distances with short time interval (5 s) sampling. The variation of concentration was high, and wind direction had a crucial effect on dust dispersion. The impact of weather conditions, such as temperature and relative humidity, on dust concentration were inconsistent. The dust produced during drilling was mainly coarse-grained an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Neves et al, 39 in their study reported that adherence to PPE usage is determined by individual safety values and beliefs. Several studies have found that stone crushing is the main source of dust in stone quarries 16‐18 . This was observed in the quarries visited.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Neves et al, 39 in their study reported that adherence to PPE usage is determined by individual safety values and beliefs. Several studies have found that stone crushing is the main source of dust in stone quarries 16‐18 . This was observed in the quarries visited.…”
Section: Discussionmentioning
confidence: 90%
“…Quarry workers' distance away from the crusher (main dust source) and the use of required PPEs are important in determining the magnitude of dust exposure. Crushing is the most significant dust source in stone quarries and dust concentration decreases with increasing distance away from the crusher 16‐18 . Quarry workers are faced with varying concentrations of silica dust depending on the working location.…”
Section: Introductionmentioning
confidence: 99%
“…Of the analysed studies, only one [43] was conducted in a construction-site environment; all other studies concerned mines or quarry sites. The exploited materials were, from the most commonly to least commonly exploited: coal [6,22,[30][31][32]41,44,52,56], iron [25,42], limestone [28,53], aggregates [24,51], taconite [47], granite [46], sandstone [55], copper [45], gold [48], platinum [54], and manganese [25].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the experimental protocol of each paper, only 15 out of the 24 papers referred to dust-particle size [6,22,24,25,28,31,[43][44][45]48,49,51,52,55,56]. The remaining papers did not specify this parameter, despite mentioning "respirable dust" [41,47,53], "respirable and inhalable" [42,54], or just "dust" [32,50].…”
mentioning
confidence: 99%